Intersecting factors in designing youth interventions in the pig value chain in Mukono and Masaka, Uganda - Namatovu, Jane; Njuguna-Mungai, Esther; Farnworth, Cathy; Ahumuza, Ronnie; Wairagala, Pamela; Achandi, Esther Leah; Lukuyu, Ben A.; Ouma, Emily A.; Galiè, Alessandra (International Livestock Research Institute, 2024)
Youth unemployment in Africa is a big challenge (Sumberg, et al., 2021; Asciutti et al., 2016), and as a result, a number of programs have been initiated to create job opportunities for the youth (Filmer and Fox, 2014). A renewed emphasis has been placed on the potential of the agricultural sector as a source of youth employment (MAAIF, 2017). Through these efforts, progress has been made in understanding youth engagement in agriculture and promoting farming as a business through market linkages, inputs (seeds, chemicals), training/capacity building, providing start-up capital and working through groups (Rietveld, et al., 2020; Turolla et al., 2017). Relatively limited efforts, however, have been undertaken on youth employment in the livestock sector (Nchanji et al., 2023).